Paper-based versus digital-based learning among undergraduate medical, nursing and pharmaceutical students in Japan: a cross-sectional study - Takashi Tatsuse; Masaaki Yamada; Michikazu Sekine (BMJ Open, 2024)
Objective Since the emergence of COVID-19, university education has drastically transformed into digital-based learning (DBL). Online education has been well recognised as a promising mode of teaching; however, only a limited number of studies have reported the students’ preferred format for academic learning.Design Cross-sectional.Setting The study was conducted in a university setting in Japan. A Google Forms online questionnaire was distributed to the participants between April and May 2022.Participants A total of 939 undergraduate medical, nursing and pharmaceutical students in the pre-clinical grade were recruited, and 344 were included in the final analysis.Primary and secondary outcome The questionnaire assessed students’ format preferences between paper-based learning (PBL) and DBL as it pertained to academic performance and eyestrain. In terms of academic performance, comprehension, memory retention and absorption (concentration) were assessed. We also explored the association between students’ daily time spent using DBL and their digital preference by the Cochran-Armitage trend test and logistic regression analysis.Results A total of 344 (191 medical, 73 nursing and 80 pharmaceutical) university students completed the questionnaire (response rate 36.6%). An even distribution was observed in the preferred learning format for comprehension: PBL (32.0%), both formats equivalent (32.8%) and DBL (35.2%; digital preference). Only few students preferred DBL for memory retention (6.1%), absorption (6.7%) and eyestrain (1.2%). Although a positive association was observed between daily time spent using DBL and digital preference for comprehension, there was no association for memory retention, absorption and eyestrain.Conclusion Among university students, DBL was just as preferred as PBL for comprehension; however, only a few students reported that DBL was better in terms of memory retention, absorption and eyestrain. A learning environment where students can study using PBL should be continued.